2010
DOI: 10.1253/circj.cj-10-0267
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Prevention Trial of Coronary Restenosis and Cardiac Remodeling After ST-Elevated Acute Myocardial Infarction (EPOC-AMI) - A Pilot, Randomized, Placebo-Controlled Study -

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp arly primary percutaneous coronary intervention (PCI) gives the higher rate of recanalization, contributing to decrease in prevalence of cardiac events and improvement of left ventricular (LV) contractility and survival prognosis. 1-3 Although additional therapies have been reported for cardioprotection after acute myocardial infarction (AMI), 4-6 LV remodeling after AMI is complicated by cardiac failure accompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 38 publications
(36 reference statements)
2
45
0
Order By: Relevance
“…52 In contrast, a low dose of erythropoietin appears to be cardioprotective. 54, 55 Platelet activation by a high-dose of erythropoietin and the existence of an optimal dose for limiting infarct size will explain the dose-dependent discrepancy of erythropoietin-induced cardioprotection. 56-58 Therefore, a large-scale, doubleblinded, placebo-controlled study is being conducted to clarify the effects of a low dose of erythropoietin on cardiac function after 6 months in patients with AMI who received successful PCI in Japan (UMIN000005721).…”
Section: Ischemic Postconditioningmentioning
confidence: 99%
“…52 In contrast, a low dose of erythropoietin appears to be cardioprotective. 54, 55 Platelet activation by a high-dose of erythropoietin and the existence of an optimal dose for limiting infarct size will explain the dose-dependent discrepancy of erythropoietin-induced cardioprotection. 56-58 Therefore, a large-scale, doubleblinded, placebo-controlled study is being conducted to clarify the effects of a low dose of erythropoietin on cardiac function after 6 months in patients with AMI who received successful PCI in Japan (UMIN000005721).…”
Section: Ischemic Postconditioningmentioning
confidence: 99%
“…49,50) GATA-4 has been shown to play a role as a survival factor that can break the vicious cycle of postinfarction heart failure. That EPO-ERK activation stabilizes GATA-4 activity by activating phosphorylation and diminishing ubiquitination of GATA-4 provides a clue into a possible molecular mechanism of the previously reported cardioprotective effects of EPO.…”
Section: Discussionmentioning
confidence: 99%
“…Two small studies showed positive effects. Taniguchi et al 60 studied the effect of low-dose erythropoietin (6000 IU during PCI for acute MI) on in-stent neointimal volume, myocardial infarct size, and LV function. There was no significant difference in absolute infarct size between groups at 4 days or 6 months.…”
Section: Other Older and Newer Pharmacological Approaches Erythropoietinmentioning
confidence: 99%
“…60,61 Large REVEAL study showed no reduction of infarct size 62,63 and several other recent trials were negative for infarct size reduction [64][65][66][67] Glucose-insulin-potassium Recent large IMMEDIATE trial assessed 12 h GIK infusion started out-of-hospital. No decrease in progression to enzymatic evidence of infarction.…”
Section: Erythropoietinmentioning
confidence: 99%